Potensi Probiotik sebagai Agen Terapi Rhinitis Alergi Terbarukan: Literature Review pada Uji Klinis - Giska Tri Putri; Aloysius Krishartadi Damar Bawono; Gresia Rosi Chofifah; Nisrina Zalfa Fatin; Aulia Fifi Malika; Julian Mahendra; Faalih Mathul Hajariyah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Allergic rhinitis is a chronic inflammatory disease that occurs widely in the global population. This disease is related to the body's hypersensitivity to allergens from the external environment. Available therapy for allergic rhinitis is only symptomatic, while primary therapy has several problems, such as access, time, and cost. Research related to renewable rhinitis therapy is needed, one of which is the use of probiotics as a therapeutic agent. The research method used was a literature review through the PubMed and GoogleScholar databases using the keywords "Rhinitis," "Probiotics," "NSS," and "TNSS." The literature search process was carried out systematically by applying several inclusion criteria. In total, four final articles were obtained from a total of 27 available articles. The results of nasal symptom score (NSS) and total nasal symptom score (TNSS) measurements in several analyzed studies indicated the potential of probiotics such as NVP1703, the combination of B. animalis Subsp. Lactis BB12 with Enterococcus faecium L3, and Lacticaseibacillus paracasei GM-080 in treating allergic rhinitis symptoms. Probiotics as a renewable therapeutic agent for allergic rhinitis have been shown to reduce symptoms, as measured by a decrease in mean NSS and TNSS values. The antiallergic activity of probiotics occurs through regulatory mechanisms of Th1 cells, Th2 cells, inflammatory mediators, and the production of pro-inflammatory antagonist compounds.